Experimental Analysis for Thermal Performance of Heat Distribution System in hot BoP of 2 kW‐class SOFC1. Issue 4 (8th July 2019) - Kim, Y. B.; Kim, E.; Yoon, J.; Song, H. W.
Abstract: This study designed and tested the components of hot balance of plant (BoP) included in a 2 kW‐class solid oxide fuel cell (SOFC) system and evaluated their thermal performance. A Pd/Pt catalytic combustor was fabricated as a component of hot BoP, and integrated hot BoP with an efficient structure was fabricated by calculating the heat transfer rates of the air preheater and steam generator through a theoretical design method. It was found that placement of the air preheater in front of the steam generator exhibited the most excellent heat transfer rate. Moreover, the heat transfer rates of the designed air preheater and steam generator exceeded the upper limit of the maximum possible heat transfer of the preheated air and the water. In experimental results, the thermal efficiency of the integrated system was 60% at the reference heat input and 70% at low heat input. The oxidizing flame of the catalyst was visualized, and the oxidation characteristics of the catalytic combustor were analyzed by measuring the concentration of the final discharged gas, that is, carbon monoxide (CO). This study helps to fabricate the integrated hot BoP system, as it provides design techniques and efficient system configuration.